Política monetária e o canal do crédito bancário: verificação da existência do canal de crédito no Brasil no período de janeiro 2000 a março 2007 - Silva, Sueli Maria Bresciani (2008)
The objective of this paper is to achieve empirical evidences which support the importance of bank lending channel in the transmission of monetary policy in Brasil from jan 2000 to mar 2007. The methodology used was based on the relationship between time series, using data from monetary policy, credit market, money market and inflation. Econometric tests followed using VAR and VEC models to analyze these series. It was observed the behavior of debt issuance market as an alternative source of external funding for companies, besides bank debt, in order to evaluate the existence of a displacement to other external financing sources due to a monetary shock. The conclusion that emerges from econometric tests indicates the importance of bank debt in monetary policy transmission, identified through cause effects and reactions of impulse-response found. The observation of increases in company’s private issuances, in order to attend its external financing needs, indicates that credit reductions, after monetary concentration, occurs through bank’s credit supply side.